Emergence of the delta variant and risk of SARS-CoV-2 infection in secondary school students and staff: Prospective surveillance in 18 schools, England. (March 2022) - Ladhani, Shamez N.; Ireland, Georgina; Baawuah, Frances; Beckmann, Joanne; Okike, Ifeanyichukwu O.; Ahmad, Shazaad; Garstang, Joanna; Brent, Andrew J.; Brent, Bernadette; Aiano, Felicity; Amin-Chowdhury, Zahin; Kall, Meaghan; et al.
Summary: Background: The role of educational settings in SARS-CoV-2 infection and transmission remains controversial. We investigated SARS-CoV-2 infection, seroprevalence, and seroconversion rates in secondary schools during the 2020/21 academic year, which included the emergence of the more transmissible alpha and delta variants, in England. Methods: The UK Health Security Agency (UKHSA) initiated prospective surveillance in 18 urban English secondary schools. Participants had nasal swabs for SARS-CoV-2 RT-PCR and blood sampling for SARS-CoV-2 nucleoprotein and spike protein antibodies at the start (Round 1: September-October 2020) and end (Round 2: December 2020) of the autumn term, when schools reopened after national lockdown was imposed in January 2021 (Round 3: March-April 2021), and end of the academic year (Round 4: May-July 2021). Findings: We enrolled 2314 participants (1277 students, 1037 staff; one participant had missing data for PCR testing). In-school testing identified 31 PCR-positive participants (20 students, 11 staff). Another 247 confirmed cases (112 students, 135 staff) were identified after linkage with national surveillance data, giving an overall positivity rate of 12.0% (278/2313; staff: 14.1%, 146/1037  vs students: 10.3%, 132/1276; p  = 0.006). Trends were similar to national infection data. Nucleoprotein-antibody seroprevalence increased for students and staff between Rounds 1 and 3 but were similar between Rounds 3 and 4, when the delta variant was the dominant circulating strain. Overall, Nucleoprotein-antibody seroconversion was 18.4% (137/744) in staff and 18.8% (146/778) in students, while Spike-antibody seroconversion was higher in staff (72.8%, 525/721) than students (21.3%, 163/764) because of vaccination. Interpretation: SARS-CoV-2 infection rates in secondary schools remained low when community infection rates were low, even as the delta variant was emerging in England. Funding: This study was funded by the UK Department of Health and Social Care.